A Philosophical Framework for Analyzing Educational Discourse: The Role of the Elementary Proposition - Abuduwayiti, Waliye (European Journal of Social Science Education and Research, 2025)
This paper examines the concept of elementary propositions within the philosophy of language and reinterprets their relevance for contemporary educational and social-science research. The aim of the study is to demonstrate how the structural features of propositions—such as compositionality, structurality, and intentionality—provide a conceptual framework for analyzing meaning-making in instructional communication and social discourse. The paper employs philosophical analysis as its primary method, using classical theories of propositional form as an analytical lens to explore how meaning is expressed, interpreted, and negotiated in teaching, curriculum design, and institutional communication. The findings show that propositional clarity influences learner comprehension, supports effective instructional design, and reveals how cultural and ideological meanings are embedded in public communication. The study contributes to education and social science by offering a theoretical model that links linguistic structure with practical concerns in pedagogy, discourse analysis, and the representation of knowledge.